Educational Management: What is the Role of the School Principal in the Improvement of Science Teachers' Performance? - Marlina Siregar (Jurnal Penelitian Pendidikan IPA, 2024)
Principals have an important role to play in schools in improving the performance of teachers, especially science teachers, who are often perceived by students as boring to teach. This study aimed to analyze the relationship between the role of principal and performance of science teachers in junior high school in Labuhanbatu Regency. This research is a quantitative study with a sample size of 90 junior high school teachers in Labuhanbatu Regency. Data analysis using univariate and bivariate tests. The results showed that the role of the principal was achieved (62.2%), which dominated the role of manager, educator and leader. Multiple regression test shows that the role of the principal is able to improve the performance of science teachers in the learning process (R= .57 (R2 = .325, p < .01). The conclusion of this study is that principals who fulfil their role can make a positive contribution to teachers, especially science teachers who often face barriers to developing interesting learning in the classroom. In addition, there are other aspects that principals should use to improve performance of science teachers